Análisis doctrinario y jurisprudencial del pago de la bonificación por desahucio al término de la relación laboral por retiro voluntario - Díaz Barros, Christian Leonardo (2024)
The present research work has as a main objective, to show through acts, doctrine, and law analysis the origin of severance pay at the end of a work relationship due to voluntary retirement, when the worker has decided to express the end of the relationship under that legal form and as a result given the reason of agreement in both parties. Also, it determined the Constitutionality of ordering the payment of severance pay at the end of a working relationship due to volunteering retirement, the same adjust to the principles of progressivity, inalienability, and intangibility; and it was established that the principle of In dubio pro operator must be applied in favor of the worker when the justice operators have hesitations at the moment to solve the different causes that they have in other similar cases. About the methodology, a qualitative idea was given, as the analytical, exegetical, and inductive methods, also try to compile all the data from similar legal texts, jurisprudence, and doctrine to then analyze each of them, above all the court judgments with those could notice the origin of severance pay take into account the legal base and the legal constitutional current base; it was observed unconstitutionality of ruling that denied the payment of the bonus, even when the working relationship has been in the same way for another worker. Finally, it can be noted that it does not exist a final result from the National Court of Justice through any sentence with any mandatory obligation to determine the origin of this type of labor actions, with the main idea of guaranteeing the workers; right